PERANCANGAN MEDIA PEMBELAJARAN PERHITUNGAN DASAR PADA SISWA KELAS 2 SDN 101822 PANCUR BATU BERBASIS ANDROID - Sianturi, Angel Maisya; Jamaluddin, Jamaluddin; Harianja, Eva Julia G. (Universitas Methodist Indonesia, 2024)
This study aims to design an Android-based basic calculation learning media application for SDN 101822 Pancur Batu. The application was created with the purpose of helping students learn basic calculations independently and increasing the effectiveness of learning with interactive features. To produce optimal interactive media, various methods are used, such as collecting data from literature sources, observations, and interviews with experts. In addition, the interactive media design is also carried out using Adobe Animate. After being designed, the interactive media is tested to ensure that it functions well and can improve learning effectiveness. The result of this study is a basic calculation learning media application integrated with the government curriculum and accessible by students anytime and anywhere. This application is expected to help students understand basic calculations better and more interestingly, as well as improve their learning achievement in mathematics.